The Improvement of Students’ Mathematical Reasoning Ability and Mathematical Resillience using Contextual Teaching and Learning - Assya, Lily Aulin; Putra, Harry Dwi; Sumarmo, Utari (IKIP Siliwangi, 2025)
This research is motivated by the low mathematical reasoning ability of students which is indicated by the difficulty in understanding math problems in the form of story problems, as well as the level of mathematical resilience of students in one of the private junior high schools in Indramayu towards mathematics subjects. The purpose of this study was to determine the effectiveness of Contextual Teaching And Learning Based on Augmented Reality learning which is seen based on the increase in students' mathematical reasoning abilities through Contextual Teaching And Learning Based on Augmented Reality learning And to find out the level of students' mathematical resilience. This research was conducted at a private junior high school based on an Islamic boarding school in Indramayu. The research was conducted in class IX using 2 available classes, namely class IX A with 28 students as the Experimental class and class IX B with 26 students as the Control class. This study uses a mix method with explanatory sequential design. The instruments used in this study include mathematical reasoning ability test instruments on the material of curved side space shapes and mathematical resilience scales. The results of this study indicate that Contextual Teaching and Learning based on Augmented Reality is effective in improving students' mathematical reasoning abilities and achieving student learning completion.